Study of the suffix -il in Old Galician-Portuguese - López-Viñas, Xoán (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper analyzes the form, function and meaning of the suffix -il, which forms deverbal adjectives, and rarely desubstantive adjectives, in medieval Galician-Portuguese, in order to observe its productivity in the formation of suffixed voices. In this work a comparison is also made with the Latin suffix -ilis from which it derives (and which comes from different origins). To carry out this study we start from the Corpus do Galego-Portugués Antigo, which will allow us to verify the degree of productivity or profitability of this suffix.